Information Needs of Farmers Regarding Improved Agricultural Technologies - Baldeo Singh, R. N. Padaria, Mukesh Singh, Mandavi Mishra, V. K. Chaturvedi (Indian Journal of Extension Education, 2022)
The study was conducted among 200 farm families selected from five villages of two blocks in district Gurgaon (Haryana) to investigate social, economic and communication characteristics of farmers and to know their information needs related to agriculture. The study revealed that majority of the farmers was educated up to primary, having land size 2.51 to 7.50 acres and poor extension and mass-media contacts. They needed information regarding different aspects of cultivation of wheat, rice, pigeon-pea, bajra, mustard, gram and vegetables. Majority of them needed information regarding selection of recommended varieties of different crops, vegetables and flowers, seed treatment, interpretation of soil & water testing reports, soil and water testing and management, integrated nutrient management, use of different weedicides for the control of specific weeds and time & method of application of weedicides, causes of spread of insect pests & diseases and time and methods of the control of insect, pests & diseases. A large majority also required information regarding integrated nutrient management, organic farming, protected agriculture, market and weather information, postharvest processing and value addition. Neighbor, progressive farmer, radio and KVK scientist were the most utilized sources of information by the farmers in order of merit. They suggested to have information on allied enterprises like bee-keeping, vermi-composting, mushroom cultivation etc. for additional income and employment